The effect of physical therapy on beta-endorphin levels - Bender, T.; Nagy, G.; Barna, I.; Tefner, I.; Kadas, E. (European Journal of Applied Physiology, 2007)
Beta-endorphin (ßE) is an important reliever of pain. Various stressors and certain modalities of physiotherapy are potent inducers of the release of endogenous ßE to the blood stream. Most forms of exercise also increase blood ßE level, especially when exercise intensity involves reaching the anaerobic threshold and is associated with the elevation of serum lactate level. Age, gender, and mental activity during exercise also may influence ßE levels. Publications on the potential stimulating effect of manual therapy and massage on ßE release are controversial. Sauna, mud bath, and thermal water increase ßE levels through conveying heat to the tissues. The majority of the techniques for electrical stimulation have a similar effect, which is exerted both centrally and—to a lesser extent—peripherally. However, the parameters of electrotherapy have not yet been standardised. The efficacy of analgesia and the improvement of general well-being do not necessarily correlate with ßE level. Although in addition to blood, increased brain and cerebrospinal fluid ßE levels are also associated with pain, the majority of studies have concerned blood ßE levels. In general, various modalities of physical therapy might influence endorphin levels in the serum or in the cerebrospinal fluid—this is usually manifested by elevation with potential mitigation of pain. However, a causal relationship between the elevation of blood, cerebrospinal fluid or brain ßE levels and the onset of the analgesic action cannot be demonstrated with certainty.